Rent-seeking decisions of the main participants in construction projects based on evolutionary-game and system dynamics - Zuo, Weiwei; Wang, Qiankun; Li, Peng (Journal of Civil Engineering and Management, 2022)
The performance of a construction project can be severely harmed by its participants’ rent-seeking. In order to prevent such attempt, this research integrates the evolutionary game theory with system dynamics method to simulate the impact of the change of some factors that may cause/reduce rent-seeking. Based on the analysis of the behavioral characteristics and interactive relationships of the main participants (the owner, supervisor, and contractor), an evolutionary game model is constructed and simulated with the method of system dynamics based on the replication dynamic equation of the mixed strategy solution of the three-party static game model. By assigning the parameters of project scale, supervision likelihood, supervision success rate, supervision cost, and penalty intensity, the interaction mechanism of the participants on each factor is revealed through a case-based simulation. The results show that the impacts of these factors on participants’ rent-seeking decisions are significantly different. Furthermore, some management suggestions are provided to prevent rent-seeking for project owner according to the research conclusions. This research can help the project owners take proper measures to prevent rent-seeking of the supervisors and the contractors to improve the performances of the projects.